Airway management of post burn contracture neck – a case report - T.N. Chethanananda; Sanjay B.G; Aasthaa Aasthaa; Mahalakshmi Mahalakshmi; Chaithra G.V (International Journal of Medical Research and Review, 2015)
The Anaesthetic management of patients with post burn contracture release poses many problems to anaesthesiologist. Airway management in such cases is still challenging to anaesthesiologist as the contracture and deformity due to fibrous tissue resulting in non-alignment of oral, pharyngeal and laryngeal planes, makes laryngoscopy and endotracheal intubation very difficult or impossible and this can result in many life threatening and serious complications. We report the successful airway management of a patient with restricted neck extension and fixed flexion deformity by awake nasal fibreoptic bronchoscope guided nasotracheal intubation.